Inventory of orchids in Mount Tinombala Natural Reserve, Tolitoli Regency, Central Sulawesi - DYAN MEININGSASI SISWOYO PUTRI (Biodiversitas Journal of Biological Diversity, 2006)
The aims of the research were to inventory the flora of Sulawesi, especially orchids in the Mount Tinombala Natural Reserve and to collect the plant materials for planting as a collection plants in Bali Botanical Garden. The method used in this research was explorative method at the place with altitude more than 700 m above sea level. The result of the research was 50 collection number of orchids which was consist of 72 specimens, 19 families and 24 species found in the Mount Tinombala Natural Reserve, Tolitoli Regency, Central Sulawesi. Two numbers of them that unidentified yet called as a genus dubious. Dendrobium and Eria were the genus that dominant in the natural reserve and one species that predicted as a new collection for the Bali Botanic Garden was Macodes petola Lindl. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: orchids, inventory, Mount Tinombala Natural Reserve, Tolitoli, Central Sulawesi